The Spiritual Relationship of Said Burkhoniddin Muhakkiki Tirmizi and Mavlono Jaloliddin Balkhi - Saidova Sayora Eshonkulovna (Zien Journals, 2021)
The following article provides a brief and theoretical look at the scientific literary works of two prominent representatives of Sufism, Said Burhaneddin Muhakkik Tirmizi and Jalal al-Din Rumi, as well as their relationship of mentors and proteges.
Keywords: Relations Between Two Great Sages; Philosophical Thoughts Of Said Burkhoniddin; The Best Example Of A Teacher And Student; Said Burkhon's Approach To The Study Of